2021
DOI: 10.1038/s42003-021-01890-z
|View full text |Cite
|
Sign up to set email alerts
|

Light control of the peptide-loading complex synchronizes antigen translocation and MHC I trafficking

Abstract: Antigen presentation via major histocompatibility complex class I (MHC I) molecules is essential to mount an adaptive immune response against pathogens and cancerous cells. To this end, the transporter associated with antigen processing (TAP) delivers snippets of the cellular proteome, resulting from proteasomal degradation, into the ER lumen. After peptide loading and editing by the peptide-loading complex (PLC), stable peptide-MHC I complexes are released for cell surface presentation. Since the process of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Recent advances in ribosome profiling and other technologies demonstrated reduced fidelity in early phases of translation. We rationalized that the early amber codon at position Tyr37 is prone to such inaccuracy. In a recent study, we observed slightly increased amber suppression efficiency by using a bicistronic translation approach . In order to circumvent the Nb mCherry background expression, we developed a new approach inspired by the translation strategy of the foot-and-mouth disease virus (Figure a, construct V).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent advances in ribosome profiling and other technologies demonstrated reduced fidelity in early phases of translation. We rationalized that the early amber codon at position Tyr37 is prone to such inaccuracy. In a recent study, we observed slightly increased amber suppression efficiency by using a bicistronic translation approach . In order to circumvent the Nb mCherry background expression, we developed a new approach inspired by the translation strategy of the foot-and-mouth disease virus (Figure a, construct V).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze PA Nb mCherry binding, we co-expressed the cognate target protein (EGFP), which can be fused to many reference proteins via a multiple cloning site. As an initial reference, we used the ER-resident transporter associated with antigen processing (TAP1). , Second, we connected both gene constructs via the foot-and-mouth disease virus ribosomal skipping site (F2A), which allows bicistronic translation of two proteins (target and nanobody) in a single ribosome passage (Figure a). , Polycistronic mRNAs are a valuable strategy for the expression of certain genes in mammalian cells that is gaining increasing recognition . Parallel protein synthesis was monitored using flow cytometry to detect the two fluorescent reporters (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This photoactivation strategy has been widely adopted in probing protein functions across different protein families. 4 Chemical modification of serine and/or threonine residues with O-GlcNAc commonly occurs on intracellular proteins. 5 Accumulating evidence has demonstrated that O-GlcNAc plays a pivotal role in controlling protein functions, ranging from subcellular localization, to protein stability, to protein−protein interactions.…”
mentioning
confidence: 99%